A biomechanical comparison of two plating techniques in lateral clavicle fractures. (July 2019) - Suter, Cyrill; von Rohr, Martina; Majewski, Martin; Dürselen, Lutz; Warnecke, Daniela; Schild, Natalie; Nowakowski, Andrej Maria
Abstract: Background: Neer Type IIb lateral clavicle fractures typically lead to dislocation of the medial fragment. Therefore, most surgeons recommend surgical treatment for such a fracture pattern. The use of a locking compression plate with a lateral extension has produced satisfactory results in various studies over recent years. Double-plate fixation is a common technique in the treatment of complex distal radius fractures. The authors use this technique as a routine procedure in the treatment of Neer type IIb fractures. In this biomechanical testing study, the mechanical properties of the two techniques were compared. Methods: On 20 clavicles from fresh frozen cadavers a Neer Type IIb fracture-like osteotomy was performed. A cyclic loading test followed by a load-to-failure test was carried out. Parameters for statistical evaluation were the stiffness at cycles 1, 100 and 17, 500 as well as the ultimate tensile load and the deformation at the point of failure. Findings: All specimens withstood the cyclic loading test without any noticeable damage. At cycles 100 and 17, 500, the double-plate technique was less stiff. Failure loads were not significantly different from each other, but deformation at the point of failure was significantly greater for the double-plate technique. Interpretation: Both techniques provided sufficient fixation to the fracture site to endure the cyclic loading test, which is supposed to simulate an incident-free week postoperatively. In summary, the double-plate technique offers biomechanically a feasible alternative to the single-plate technique in lateral clavicle fractures of Neer Type IIb. Highlights: Double-plate fixation offers a feasible alternative in Neer Typ IIb fractures. New surgical approach for lateral clavicle fracture stands under scrutiny. Biomechanical evaluation of two plating techniques for lateral clavicle fractures.